ORGANIC FOOD MARKETING MANAGEMENT - Rakić, Beba; Rakić, Mira (Economics of Agriculture, 2009)
Growing competition forces organizations to adopt marketing orientation in order to stay competitive. The purpose of this paper is to explore organic food marketing management. Main challenges in organic food marketing are marketing orientation, attitudes of organizations and consumers toward organic food, income, relation marketing, food safety, high price, sales infrastructure – distribution and promotion. Consumers' selections of organic foods are influenced by many factors including health concerns, environment, lifestyle, food quality, price and consumer's level of personal disposable income. The most important marketing decisions are: targeting, positioning, differentiation and marketing mix management.